Competitive Power of Livestock Farming Towards 2020 - Simatupang, Pantjar; Hadi, Prajogo U (Indonesian Bulletin of Animal and Veterinary Sciences, 2004)
In the decade of 1990s animal husbandry revolution started to occur and it is estimated to continue for the next 20 years. Contrary to the green revolution in which the main activator is technology innovations on the production, i.e. the discoveries of short life high-yielding varieties, the prime activator in animal husbandry revolution is the increasing demand. The demand on livestock products in the local markets is estimated to increase in line with the increase in income per capita and total population growth. It is projected that Indonesia will still have meat production deficit of around 2.7 million tons in 2020. This deficit is a local market huge opportunity to be exploited. As an archipelago, Indonesia has a less comparative superiority to develop grassfed livestock farming system, such as beef cattle, buffalo, goat and sheep, with a result that the competitive power of Indonesia lies on grain-fed livestock farming system, i.e. broiler and layer chickens. Therefore, in order to develop farming and simultaneously improve the comparative power of Indonesian livestock farming by considering the diversity of biophysical of the regions and the social economic potency (including the huge local markets), it is necessary to develop specific location technologies for grain-fed intensive farming orienting at the local market demand and at the same time also facilitate the grassfed fanning system so it does not extinct. Key words: Developing livestock farming